Fake Order dan Retur Barang dalam Jual Beli di Marketplace Shopee Perspektif Hukum Ekonomi Syariah - Moh Asra (Program Pascasarjana Universitas Ibrahimy, 2024)
Constitutionally, Indonesia is neither a religious state nor a secular state, but a state based on Pancasila. The ideology of this nation also influences the development of law in it, which is not based on religion nor adheres to the secular legal system. Based on the Pancasila philosophy, Indonesia's national legal system recognizes religious law, customary law and Western law as a source of material law in the formation of national law. The existence of Islamic law in the national legal system experienced ups and downs, due to the influence of the political power of each era of government. Transforming Islamic law into national law requires negotiation and dialectics through a friendly approach and does not trigger national disintegration. So that the process of transformation into the resulting national law can be divided into two forms, first, Islamic law is adapted into positive law in the form of organic law. Second, accommodation in the form of absorption of Islamic values ??into national law, by not using Islamic / Islamic labels. The transformation of Islamic law into national law is a manifestation of responsive and accommodative legal development. The development of a good legal system must be free from political compulsion or power. The development of a good legal system will support the implementation of good governance. Developing the country by paying attention to social aspects in a democratic way to guarantee the benefit of the nation.